Using Role-based to Implement Certificate Authority Management for Big Data - Shareef, Omar Salah F.; Sagheer, Ali Makki (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2019)
One of the big issues for dynamic organizations is managing the confidential information of big data. Improving security is needed to secure exchange of confidential documents, protection against unauthorized accesses, handling changes in the permissions and roles of people and dealing with the dynamism that can happen if any person leaves or join the system. However, there are limitations in using traditional cryptographic systems and Public Key Infrastructure (PKI) concerning flexibility and manageability. In this paper, we propose a secure and verifiable access control system that implements a Certificate Authority coupled with Role-Based Access Control to provide the permissions to the user to access data. The digital certificate is certified, issued, and revoked by a central administrator; as a result, the certificate is sent based on the role of the user. The proposed scheme has been demonstrated on a big dataset. We believe that our work can be applied to organizations that rely heavily on big data.